The BIRTH PREPAREDNESS AND COMPLICATION READINESS COUNSELING TO IMPROVE HUSBAND PREPAREDNESS - Hanna Yuanita Santoso (STIKes William Booth Surabaya, 2020)
Birth Preparedness and Complication Readiness (BP/CR) is a strategy to promote optimal care related to the management of obstetric complications. Ideally, maternal health is the joint responsibility of married couples. In the concept of Suami SIAGA, the husband is expected to be ready and aware of risks, to keep his wife from doing things that interfere with her pregnancy, and to accompany her to the nearest referral if signs of complications arise. The role of SIAGA is carried out with the aim of preventing the 3 delays that cause maternal death. This study aims to assess the effectiveness of counseling on birth preparedness and obstetric complication readiness to improve husband's preparedness in dealing with labor and obstetric complications. This was a prospective quasi experimental study with a one group pre-test-post test design. The samples were 32 husbands from pregnant women, taken using a proportional systematic random sampling technique. This sutdy was conducted in the Bandarharjo Community Health Center, Semarang City in April-July 2018. Data collection used a questionnaire given 2x (pretest and posttest) during pregnancy and a follow-up questionnaire during the puerperium. Univariate analysis yields frequency and percentage distribution. Bivariate analysis was performed using paired sample t-test. There was a significant difference in the mean score of knowledge and perceptions of husbands about the practice of BP/CR before and after the intervention (p=0.000). BP/CR counseling was effective in increasing husband's preparedness in dealing with childbirth and obstetric complications.